Bibliometric analysis of augmented reality in chemistry education over the past decade - Juan, Du; DeWitt, Dorothy (Intelektual Pustaka Media Utama, 2024)
Numerous studies have delved into the application of augmented reality (AR) in chemistry education, focusing on specific topics, equipment requirements, and advantages. However, there remains a notable dearth of research examining the evolutionary characteristics of AR in this context. This study, employing bibliometric analysis on 66 articles spanning from 2012 to 2022, reveals that research primarily revolves around pedagogical approaches and AR technology development, particularly in kindergarten to 12th grade (K-12) education. Despite the United States exhibiting the highest publication frequency, there is a significant absence of studies addressing emotions, cognition, and physiological changes. Shedding light on these research gaps, this study underscores the need for further exploration into the cognitive, emotional, and physiological aspects of AR integration in chemistry education. Ultimately, the insights gleaned from this study offer valuable guidance for researchers, educators, and practitioners alike, facilitating the advancement and effective application of augmented reality in chemistry education (ARCE).